Electronic commerce and actual problems of taxation: The key underlying issues - Teixeira, I.; Paiva, I. (Research anthology on e-commerce adoption, models, and applications for modern business, 2021)
This chapter examines the problems related to the international taxation of electronic commerce and identifies the alternative solutions that have been adopted in the current fiscal framework. The results obtained demonstrate the proposed models of e-commerce taxation based on existing international legislation, notably origin-based taxation, tax withheld at source and technology based solutions. This study argues that any legislative change should be implemented by a number of countries or through international efforts to harmonize practices, and sets out the future directions in the taxation of e-commerce. This chapter contributes to the scientific knowledge to accounting and tax research on the taxation of e-commerce.